How to listen to great music : a guide to its history, culture, and heart - Greenberg, Robert, 1954- (New York : Plume, 2011)
Presents a guide to the composers and masterpieces of Western music from medieval times up to the twenty-first century, covering such musical classifications as baroque, classical, romantic, and modern.
Understanding and listening to music -- A mad dash through the roots of Western music -- The music of the medieval Church -- A necessary and invigorating excursion into the worlds of music theory and terminology -- Emotional exuberance and intellectual control : the paradox of Baroque art -- Play it, don't say it : the rise of instrumental music -- National styles : Italy and Germany (or, Why German music will never hit your eye like a big pizza pie and Italian music will never go from best to wurst) -- Fugue it! -- Opera : the Baroque expressive revolution in action -- Opera goes to church -- A new liturgy comes of age : Lutheran Baroque sacred music -- Instrumental form in Baroque era music -- Baroque era musical genres -- Enlightened is as enlightened does : an introduction to the Classical era -- Putting it all together : Classical era musical form, part one -- Classical era musical form, part two -- Classical era orchestral genres, part one -- Classical era orchestral genres, part two -- Send in the buffone : opera in the Classical era -- A revolutionary artist for a revolutionary time : Ludwig van Beethoven -- Beethoven's compositional innovations : when the going gets tough, the tough innovate -- Isn't it Romantic? : the music of the nineteenth century -- Structural problems : formal challenges in early Romantic music -- Going beyond Beethoven : Hector Berlioz's Symphony fantastique and the program symphony -- Nineteenth-century Italian opera : Rossini and bel canto -- Giuseppe Verdi : it's all about the people--dramatic truth in Italian opera -- Nineteenth-century German opera : von Weber and Wagner, nationalism and experimentation -- Of thee I sing : musical nationalism in the nineteenth century -- Romantic nationalism, Russian style -- A modern music for a modern world -- Revolutions, evolutions, and "-isms" galore : the making of a new music in the early twentieth century -- From Russia with rhythm : Igor Stravinsky -- No waltz in the park : Arnold Schoenberg's Vienna and Expressionism -- Postlude.
"The great courses"--Spine.
Includes bibliographical references (pages 323-324) and index.
Keywords: Music appreciation; Music appreciation